(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, taking care of the welfare of employees is very important in order to ensure they do hard work toward organizational goals. The aim of this study is to establish the impact of compensation on employee retention. The objective of this research is, firstly, to evaluate the level of employee retention. Secondly, this research examines the relationship between compensation and employee retention. Lastly, determine the effect of the compensation on employee retention. This research is carried out at Bestlink College of the Philippines. Based on the result, the researchers conclude that there is no significant relationship between compensation and retention. Based on the results presented, the researchers came up with the following recommendations such as open communication between employees and management. Hold regular meetings. The employer should keep in mind the Employee Compensation strategy depending on the age of the employees. Employers can conduct employee surveys to get feedback on the current compensation package. A transparent pay policy can also help boost employee morale and trust in management, showing the company compensates its employees fairly, gives at least one jug additional for referral commission, Keeps giving the proper benefits for employees, and lastly, keeps giving the best pay structure for employees.